Rational Engineering of Hydratase from Lactobacillus acidophilus Reveals Critical Residues Directing Substrate Specificity and Regioselectivity. (20th November 2019) - Eser, Bekir Engin; Poborsky, Michal; Dai, Rongrong; Kishino, Shigenobu; Ljubic, Anita; Takeuchi, Michiki; Jacobsen, Charlotte; Ogawa, Jun; Kristensen, Peter; Guo, Zheng
Abstract: Enzymatic conversion of fatty acids (FAs) by fatty acid hydratases (FAHs) presents a green and efficient route for high‐value hydroxy fatty acid (HFA) production. However, limited diversity was achieved among HFAs, to date, with respect to chain length and hydroxy position. In this study, two highly similar FAHs from Lactobacillus acidophilus were compared: FA‐HY2 has a narrow substrate scope and strict regioselectivity, whereas FA‐HY1 utilizes longer chain substrates and hydrates various double‐bond positions. It is revealed that three active‐site residues play a remarkable role in directing substrate specificity and regioselectivity of hydration. If these residues on FA‐HY2 are mutated to the corresponding ones in FA‐HY1, a significant expansion of substrate scope and a distinct enhancement in hydration of double bonds towards the ω‐end of FAs is observed. A three‐residue mutant of FA‐HY2 (TM‐FA‐HY2) displayed an impressive reversal of regioselectivity towards linoleic acid, shifting the ratio of the HFA regioisomers (10‐OH/13‐OH) from 99:1 to 12:88. Notable changes in regioselectivity were also observed for arachidonic acid and for C18 polyunsaturated fatty acid substrates. In addition, TM‐FA‐HY2 converted eicosapentaenoic acid into its 12‐hydroxy product with high conversion at the preparative scale. Furthermore, it is demonstrated that microalgae are a source of diverse FAs for HFA production. This study paves the way for tailor‐made FAH design to enable the production of diverse HFAs for various applications from the polymer industry to medical fields. Abstract : Dictated by only a few : Comparative analysis of the active‐site residues of two fatty acid hydratases from L. acidophilus, which have high sequence homology, but distinct substrate specificity and regioselectivity, reveal three critical amino acids that play a remarkable role in directing substrate specificity and regioselectivity of hydration.